Fenomena Politk Uang Dalam Pemilihan Umum Legistlatif - Mutiara Cindy Fatihah; Siti Siska Cutikawati; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Elections are a democratic process used to elect government leaders and represent the community in government institutions. Money politics is a phenomenon that often occurs in general elections. Money political campaigns are carried out by individuals or groups who use money to influence people's behavior in elections. The aim of this article focuses on the phenomenon of money politics that occurs in society during the campaign period for legislative candidates in the 2024 elections at the neighborhood level and to find out the factors that cause money politics to occur. The form of money politics carried out includes providing basic necessities, money and health services to voters to win votes in legislative elections. This research was conducted using a qualitative research approach, collecting data through interviews and literature reviews. The results of this research show that not all people are influenced by political choices through money politics.